Chapter Penser la phase perdue du modernisme russe - Livak, Leonid (Biblioteca di Studi Slavistici, 2017)
This paper proposes a revision of Russian modernism's politically-motivated chronology and geography through the integration of two academic subfields - modernist and exilic studies. Such an integrative approach allows us better to position Russian modernist culture vis-à-vis its western counterparts, returning our research subject to its original context in the larger, international modernist field. The paper will subsequently offer a tentative sketch of the aesthetic and philosophical premises of late Russian modernism against the backdrop of western modernist practices in the 1930s.